Lactobacillus paracasei 259 alleviates hyperuricemia in rats by decreasing uric acid and modulating the gut microbiota - Bi, Chengming; Zhang, Lanjun; Liu, Jingya; Chen, Lianhong (Frontiers in Nutrition, 2024)
Hyperuricemia (HUA) is a metabolic disease arising from abnormal purine metabolism. It contributes to an increased risk of kidney damage. The present study aimed to investigate the uric acid (UA)-lowering effects of Lactobacillus paracasei 259 isolated from yak yogurt and explore its underlying mechanisms. Our results revealed that L. paracasei 259 decreased the UA levels in rats and inhibited the serum activities of xanthine oxidase. In addition, L. paracasei 259 reduced the levels of pro-inflammatory cytokines (tumor necrosis factor (TNF)-α, interleukin (IL)-1β, and IL-6) in the kidney and altered the expressions of UA transporters (ABC transporter 2 (ABCG2), PDZ domain containing 1 (PDZK1), urate transporter 1 (URAT1), and sodium-phosphate cotransporter type 4 (NPT4)) to near normal levels. Moreover, it increased the abundance of beneficial bacteria in the gut and recovered the gut microbiota composition, promoting the production of short-chain fatty acids (SCFAs). These findings suggested that L. paracasei 259 can potentially be used to decrease UA levels, repair kidney damage, regulate gut microbiota, and alleviate HUA.